PENGEMBANGAN INSTRUMEN TES ESSAY KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI IKATAN KIMIA KELAS X SMA/MA - Jumadi Sihombing (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to produce an essay test instrument for critical thinking skills on chemical bonding material and to know the validity, reliability, distinguishing features, and the difficulty level of the test instrument. The research method uses the ADDIE model with five stages namely analyze, design, develop, implementation, & evaluation. In this research formative evaluation is done, meaning that the evaluation stage is carried out at the end of each stage. The test developed in the study consisted of eight essay items, referring to 10 indicators of critical thinking according to Ennis. Validation of items was done by three validators. Based on the validity according to the experts obtained an average of every aspect, namely 95% material, 96.87% construction and 91.15% language with an overall average score of 94.34% validation has a valid category. Eight valid questions were tested on 20 students. The calculation of the reliability coefficient (r11) with the Alpha Cronbach formula was obtained at 0.65 in the high category, the distinguishing power had an average value of 0.26 in enough categories and the difficulty level of the questions had an average value of 0.42 in the medium category. The developed test instrument is declared valid, reliable, has a good differentiating power, and the level of difficulty of the questions that are being made so that it can be used as a measuring tool to determine students' critical thinking skills.Key word: Research & development, critical thinking test instrument,chemical bonding